Sustainable potato farming in Shandong Province, China: a comprehensive analysis of organic fertilizer applications - Zhang, Meiling; Xu, Xuanguo; Ning, Wenping; Zhang, Fuhong; Sarkar, Apurbo (Frontiers in Sustainable Food Systems, 2024)
Introduction The potato holds the distinction of being the world’s largest non-cereal food crop and ensuring its sustainable production is imperative for global food security. Notably, China leads in both the planting area and output of potatoes globally, cementing its crucial role in the nation’s agricultural economy. A scientific assessment of the effectiveness of organic fertilizers on potato cultivation can significantly contribute to the promotion of sustainable agriculture. Methods This study utilizes a Propensity Score Matching (PSM) model and introduces a novel cost-efficiency approach to analyze and evaluate the production efficiency and economic impact of organic fertilizer application among 546 potato growers in Shandong. Results The research findings reveal the following: Firstly, compared to the control group without organic fertilizer application, it is evident that the use of organic fertilizers enhances production technology efficiency, labor productivity, land productivity, and net profit per unit by 3.6%, 1588.47 kg/person, 16346.77 kg/ha, and 16135.32 yuan/ha, respectively. Secondly, an examination of cost efficiency among growers with different production scales indicates that those with a planting scale of 0.667-1.333 hectares demonstrate relatively high production efficiency across multiple factors. Additionally, there is an observable inverted U-shaped trend in the relationship between planting scale and production efficiency. Thirdly, the continuous application of organic fertilizers proves advantageous in mitigating inefficiencies in investment techniques, leading to cost savings and efficiency improvements in potato cultivation. Discussion Consequently, it is recommended that the government and relevant departments enhance technical support, elevate professional training programs, and optimize the allocation of input factors. These measures aim to encourage farmers to adopt organic fertilizers, thereby promoting sustainable agricultural practices.